Chlamydia trachomatis infection among sexually active young women in Italy. Issue 4 (1st August 2002) - Latino, M A; Bello, L; Lanza, A; Leotta, E; Tersiev, P; De Intinis, G; Spagnolo, E; Smirne, C; Grio, R
Abstract : Objectives: Chlamydia trachomatis infection is the most common sexually transmitted disease among sexually active adolescents and young adults in Europe. The goal of this study was to determine the prevalence of C trachomatis among young women in Turin, Italy, and the correlation between some risk factors and C trachomatis infection. Methods: In our study 3314 sexually active women between the ages of 14 and 25 were screened for C trachomatis by ligase chain reaction (LCR) using cervical swabs during the period 1997–2000 at the Turin School of Medicine. All the patients answered a specific questionnaire. Results: In our analysis the prevalence of C trachomatis infection was found to be 3.5%, and the average age among the infected patients was 22.12 years. Statistical analysis was performed using the χ 2 test. A p value <0.05 was considered significant. A correlation was found between a positive result and: membership of east European and central northern Africa populations (p<0.001), low levels of education (p<0.001), age at the first intercourse (p=0.006), the presence of symptoms in the women (p<0.001), and the number of sexual partners in the preceding 6 months (p<0.001). No statistically significant difference was found among the contraceptive methods used whether hormonal or a barrier type and with the subjective symptoms of the partner. Conclusion: Frequent microbiological examinations are desirable for patients whose anamnesis shows an increased risk of contracting sexually transmitted infections in order to avoid long term complications from misdiagnosed or asymptomatic pathologies; this often happens with C trachomatis infection.